ER stress-induced YAP upregulation leads to chondrocyte phenotype loss in age-related osteoarthritis - Gao, Yanchun; Wei, Haifeng; Peng, Xiaoyuan; Wang, Chenchen; Zhu, Hongyi; Yin, Junhui (Frontiers in Pharmacology, 2024)
Background Osteoarthritis (OA) is a common degenerative joint disease, leading to pain and restricted mobility. Age-related endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of OA, but the underlying mechanisms remain unclear. This study aims to explore the relationship between age-related ER stress, YAP overexpression, and chondrocyte phenotype loss in the development of OA. Methods Cartilage samples were collected from patients undergoing amputation, and age-related ER stress markers and YAP expression were assessed using immunohistochemical staining and qPCR. Transgenic mice with cartilage-specific YAP overexpression (YAPOE) were created, and Pamrevlumab was administered to evaluate its therapeutic effects. Results Higher expression of ER stress markers and YAP were showed in aged tissues compared to younger tissues. YAP overexpression led to decreased levels of cartilage phenotype markers and increased osteogenesis-related proteins. In vivo, YAPOE mice exhibited OA-like cartilage degeneration, which was mitigated by Pamrevlumab treatment. Conclusion Age-related ER stress induces YAP overexpression, contributing to OA pathogenesis. Pamrevlumab effectively prevents this phenotype loss in YAPOE mice, suggesting its potential as a therapeutic agent for OA. These findings provide new insights into the molecular mechanisms of OA and highlight the importance of targeting the ER stress-YAP-CTGF signaling pathway in OA treatment and prevention.